MUSTAHIK ECONOMIC EMPOWERMENT STRATEGY THROUGH THE PRODUCTIVE ZAKAT PROGRAM: A QUALITATIVE STUDY ON LAZNAS BMH - Rohsyiandi Santika; Eko Muliansyah (Institut Pendidikan Tapanuli Selatan, 2026)
The productive zakat program serves as a strategic instrument in the economic empowerment of mustahik to achieve sustainable welfare and financial independence, as implemented by LAZNAS BMH. This research analyzes empowerment strategies, implementation processes, economic and non-economic impacts, supporting and inhibiting factors of the productive zakat program, as well as its contribution to the paradigm shift in Islamic philanthropy from consumptive to productive. A qualitative approach using a case study method was employed, involving in-depth interviews with managers, mustahik, partners, and community figures, analyzed thematically using NVivo. The results indicate a structured strategy encompassing potential-based selection, provision of business capital/tools, and intensive mentoring that enhances mustahik's skills, business management, and independent mindset. Positive impacts include increased income, family economic stability, reduced dependence on aid, as well as improved self-confidence and motivation. The main supporting factors are mustahik commitment, mentoring, and social support, while inhibitors include business capacity limitations, market access, and mentoring resources. This study fills the literature gap on productive zakat implementation in zakat amil institutions, emphasizes the need for comprehensive regulations to professionalize amil, and recommends a sharia-based empowerment framework for other zakat institutions to address structural poverty.